Diagnostic error assessment and associated harm of endoscopic ultrasound‐guided fine‐needle aspiration of neuroendocrine neoplasms of the pancreas. Issue 11 (9th July 2013) - Hooper, Kari; Mukhtar, Faisal; Li, Shaoying; Eltoum, Isam A.
Abstract : BACKGROUND: Over the past decade, the standardization of error classification in anatomic pathology has become an important issue. The objective of the current study was to assess the extent of errors occurring in the cytopathologic diagnosis of neuroendocrine lesions of the pancreas, and to classify these errors and their associated harm. METHODS: Information on all cases diagnosed as a neuroendocrine neoplasm either by endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) in cytology or by surgical pathology between 2000 and 2012 was collected. Using standardized error and harm classification, the authors reviewed the cytology and surgical pathology material and evaluated the type and the cause of diagnostic errors and their impact on the patient. RESULTS: A total of 177 patients who underwent EUS‐FNA were diagnosed with a neuroendocrine neoplasm either by cytology or surgical pathology. Eighty of these cases had surgical follow‐up available at the study institution. Of these 80 cases, 56 had an adequate cell block and immunohistochemistry was performed. There were 14 discrepancies noted between cytologic and surgical pathologic diagnoses. There were 9 false‐negative cases, consisting of 3 interpretation errors and 6 cytology sampling errors. There were 5 misclassifications, including 4 cases of solid pseudopapillary neoplasm and 1 case of neuroendocrine carcinoma (diagnosed as adenocarcinoma on cytology). There were no surgical pathology errors noted. All errors were associated with no or minor harm. CONCLUSIONS: EUS‐FNA of pancreatic neuroendocrine neoplasms has excellent diagnostic performance, with no false‐positive diagnoses reported. When an adequate sample is obtained, the most significant error is misclassification, which is most often associated with solid pseudopapillary neoplasm. The harm associated with diagnostic errors is at most minor. Cancer (Cancer Cytopathol) 2013;121:653–60 . © 2013 American Cancer Society . Abstract : Endoscopic ultrasound‐guided fine‐needle aspiration of pancreatic neuroendocrine neoplasms has excellent diagnostic performance, with no false‐positive diagnoses reported. When an adequate sample is obtained, the most significant error is misclassification, which is most often associated with a solid pseudopapillary neoplasm. The harm associated with diagnostic errors are at most minor.